2021
DOI: 10.1155/2021/1336762
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial Intelligence-Based Echocardiographic Left Atrial Volume Measurement with Pulmonary Vein Comparison

Abstract: This paper combines echocardiographic signal processing and artificial intelligence technology to propose a deep neural network model adapted to echocardiographic signals to achieve left atrial volume measurement and automatic assessment of pulmonary veins efficiently and quickly. Based on the echocardiographic signal generation mechanism and detection method, an experimental scheme for the echocardiographic signal acquisition was designed. The echocardiographic signal data of healthy subjects were measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…The use of AI has been applied to the whole echocardiography setting (i.e. left ventricular systolic 23,24 and diastolic [25][26][27] function, to right ventricular function 28 , assessment of heart valve diseases 29 , diagnosis of congenital heart diseases 30 ) and also to predict of FR, with encouraging results. For instance, Bataille et al 31 showed that machine learning models predicted FR with comparable accuracy to the hemodynamic response to passive leg raising, and evaluation of the IVC was among the key variables identified by the model, together with other Doppler derived parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of AI has been applied to the whole echocardiography setting (i.e. left ventricular systolic 23,24 and diastolic [25][26][27] function, to right ventricular function 28 , assessment of heart valve diseases 29 , diagnosis of congenital heart diseases 30 ) and also to predict of FR, with encouraging results. For instance, Bataille et al 31 showed that machine learning models predicted FR with comparable accuracy to the hemodynamic response to passive leg raising, and evaluation of the IVC was among the key variables identified by the model, together with other Doppler derived parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, also echocardiography is experiencing a significant expansion of AI applications that might help daily practice. Indeed, AI has been used for the assessment of left ventricular systolic 23,24 and diastolic [25][26][27] function, right ventricular function 28 , but also for the evaluation of heart valve 29 and congenital heart diseases 30 . Moreover, machine learning has been developed for predicting FR at patient's bedside 31 with preliminary data on the implementation of AI for IVC assessment 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these, also echocardiography is experiencing a significant expansion of AI applications that might help daily practice. Indeed, AI has been used for the assessment of left ventricular systolic [ 23 , 24 ] and diastolic [ 25 27 ] function, right ventricular function [ 28 ], but also for the evaluation of heart valve [ 29 ] and congenital heart diseases [ 30 ]. Moreover, machine learning has been developed for predicting FR at patient’s bedside [ 31 ] with preliminary data on the implementation of AI for IVC assessment [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of artificial intelligence (AI) is in great expansion in several medical fields, including echocardiography. For instance, AI has been applied to the estimation of left ventricular systolic [ 24 , 25 ] and diastolic [ 26 28 ] function, to right ventricular function [ 29 ], but it has also been adopted for assessment of heart valve diseases [ 30 , 31 ] and for diagnosis of congenital heart diseases [ 32 ]. Furthermore, machine learning methods have been developed for the improvement of bedside prediction of FR [ 33 ], and preliminary experiences with AI in the assessment of IVCc have been reported [ 34 ].…”
Section: Introductionmentioning
confidence: 99%